Development of the Gambo Jumputan Batik craft industry as a local potential in the Musi Banyuasin Region - Aldri Oktanedi; Maulida Masyitoh (Privietlab, 2025)
Toman Village has agricultural potential for development, one of which is the use of natural dyes from gambier sap waste as the main ingredient for batik dyes. Besides functioning as a natural dye, it also maintains the environmental ecosystem. The batik industry in Toman Village is growing rapidly; however, it faces many challenges in developing its business. Researchers studying this matter aim to analyze the problems faced by the Jumputan Gambo batik industry and formulate strategies for its development in Toman Village. A descriptive qualitative method with a case study strategy was used. The data in this study were collected through observations and in-depth interviews with each research participant. The results showed that the batik handicraft industry has great potential to develop and plays an important role in sustaining people's lives. However, its development has not been maximized and has not received significant support from related parties. The small batik industry faces many challenges in the form of non-optimal work productivity of craftsmen, slow regeneration, inability to engage in online marketing, and Jumputan batik Gambo cloth products are still fixated on traditional designs and colors or patterns, so that the market segment is limited and capital constraints. The efforts that can be made to develop batik include strengthening access to market information and financial aspects, increasing the competence of batik business actors to innovate and create new products or motifs, encouraging batik business actors to collaborate with other parties, and building partner commitments to mitigate market uncertainty.